HUBUNGAN KECEPATAN LARI 60 METER DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA PUTRA KELAS XI JURUSAN ILMU PENGETAHUAN SOSIAL 2 SMAN 11 PEKANBARU - Hermansyah, Fauzi; ', Saripin; Wijayanti, Niputu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The object of this research is to find the correlation between running speed 60 meters and the long jump result. In this research, the writer found that there are a significant correlation between running speed 60 meters and the long jump result. It was shown by the value of r is 0.897. It means that if the score of running speed is good, so, the score of the long jump will be good. Besides that, it means that there are a positive correlation between running speed 60 meters and the long jump result. This research use Correlation Pearson Product Moment as a method. The writer was taken the research at SMAN 11 Pekanbaru with the boy’s students of XI IPS 2 as the sample.Keywords: Correlation, Speed, Long Jump, Running, 60 meters